Development of Embodied Sense of Self Scale (ESSS): Exploring Everyday Experiences Induced by Anomalous Self-Representation - Asai, Tomohisa; Kanayama, Noriaki; Imaizumi, Shu; Koyama, Shinichi; Kaganoi, Seiji (Frontiers in Psychology, 2016)
The scientific exploration of the self has progressed, with much attention focused on the embodied sense of self (ESS). Empirical studies have suggested the mechanisms for self-representation. On the other hand, less attention has been paid to the subjectivity itself of the self. With reference to previous studies, the current study collected items that reflect the ESS and statistically extracted three factors for it: Ownership, Agency, and Narrative. The developed questionnaire (Embodied Sense of Self Scale, ESSS) showed good enough validity and reliability for practical use. Furthermore, ESSS discriminated schizophrenia, a disorder of the ESS, from controls. We discuss the factorial structure of ESS and the relationship among factors on the basis of the current results.